The mid-infrared spectroscopy: A novel non-invasive diagnostic tool for NASH diagnosis in severe obesity - Anty, Rodolphe; Morvan, Marie; Le Corvec, Maëna; Canivet, Clémence M; Patouraux, Stéphanie; Gugenheim, Jean; Bonnafous, Stéphanie; Bailly-Maitre, Béatrice; Sire, Olivier; Tariel, Hugues; Bernard, Jérôme; Piche, Thierry; et al. (JHEP reports, 2019)
There is an urgent medical need to develop non-invasive tests for non-alcoholic steatohepatitis (NASH). This study evaluates the diagnostic performance of an innovative model based on mid-infrared (MIR) spectroscopy for the diagnosis of NASH. Severely obese patients who underwent a bariatric procedure at the University Hospital of Nice, France (n = 395) were prospectively recruited. The clinico-biological characteristics were measured prior to surgery. Liver biopsies were collected during the surgical procedure and assessed by a pathologist. A training group (316 patients, NASH: 16.8%) and a validation group (79 patients, NASH: 16.5%) were randomly defined. MIR spectra were acquired by fiber evanescent wave spectroscopy, using chalcogenide glass fiber optic sensors and a spectrometer. This absorption spectroscopic technique delivers a spectrum that identifies the molecular composition of a sample, defining a patient's metabolic fingerprint. The areas under the receiver operating curve (AUROC) for the diagnosis of NASH were 0.82 and 0.77 in the training and validation groups, respectively. The best threshold was 0.15, which was associated with a sensitivity of 0.75 and 0.69, and a specificity of 0.72 and 0.76. Negative predictive values of 0.94 and 0.93 and positive predictive values of 0.35 and 0.36, as well as correctly classified patient rates of 72% and 75% were obtained in the training and validation groups, respectively. A composite model using aspartate aminotransferase level, triglyceride level and waist circumference alongside the MIR spectra led to an increase in AUROC (0.88 and 0.84 for the training and validations groups, respectively). MIR spectroscopy provides good sensitivity and negative predictive values for NASH screening in patients with severe obesity. There is an urgent need for tools to non-invasively diagnose and monitor non-alcoholic steatohepatitis (NASH). This study evaluates the performance of a new tool for fast NASH diagnosis based on mid-infrared (MIR) spectroscopy. Using serum samples from severely obese patients who underwent a bariatric procedure, which enabled a concomitant liver biopsy to be performed, the MIR spectroscopy model performed well in screening patients for NASH compared to a traditional, histological diagnosis. [Display omitted] •There is no validated non-invasive diagnostic tool for NASH in routine care.•NASH follow-up requires a non-invasive diagnostic method.•Using a simple drop of serum, the mid-infrared spectrum captures a patient’s metabolic fingerprint.•A model based on mid-infrared spectroscopy provides efficient NASH screening for patients with severe obesity.